Local Students’ Internship Experience In A Rural Area In Indonesia - Rina Kesia Silaban; Wolter Parlindungan Silalahi; Simion Diparuma Harianja (Journal on Education, 2023)
Students can learn how to work while honing their abilities during an internship and better comprehend how the lessons they learn in university will benefit them. This study explores and delineates the local students' experience interning in a rural area in Indonesia. The researchers adopted a phenomenology qualitative research method. Field notes, journals, and interviews were made to collect data from selected students who wrote about their daily experiences to determine their perception of the internship and gain insight into future recommendations. The results showed that the students made real progress in developing themselves, which focused on four themes: participating in the discussion in meetings, being involved in community service, joining in benchmarking and study tours, and working on lecture reports and village administration simultaneously. This study was significant because it aimed to fill a gap in the literature on undergraduate internships and to offer proof that internships would help people succeed in their careers, academic programs, and interpersonal relationships. In addition, this study has generated several ideas for more future recommendations to investigate. More diverse student groups would bring in fresh viewpoints that might deepen the research, and more perspectives from different backgrounds could extend the study's focus and offer analysis that might be useful for internship programs of other institutional kinds.